Characterization of high density SiPM non-linearity and energy resolution for prompt gamma imaging applications. (3rd July 2017) - Regazzoni, V.; Acerbi, F.; Cozzi, G.; Ferri, A.; Fiorini, C.; Paternoster, G.; Piemonte, C.; Rucatti, D.; Zappalà, G.; Zorzi, N.; Gola, A.
Abstract: Fondazione Bruno Kessler (FBK) (Trento, Italy) has recently introduced High Density (HD) and Ultra High-Density (UHD) SiPMs, featuring very small micro-cell pitch. The high cell density is a very important factor to improve the linearity of the SiPM in high-dynamic-range applications, such as the scintillation light readout in high-energy gamma-ray spectroscopy and in prompt gamma imaging for proton therapy. The energy resolution at high energies is a trade-off between the excess noise factor caused by the non-linearity of the SiPM and the photon detection efficiency of the detector. To study these effects, we developed a new setup that simulates the LYSO light emission in response to gamma photons up to 30 MeV, using a pulsed light source. We measured the non-linearity and energy resolution vs. energy of the FBK RGB-HD e RGB-UHD SiPM technologies. We considered five different cell sizes, ranging from 10 μ m up to 25 μ m. With the UHD technology we were able to observe a remarkable reduction of the SiPM non-linearity, less than 5% at 5 MeV with 10 μ m cells, which should be compared to a non-linearity of 50% with 25 μ m-cell HD-SiPMs. With the same setup, we also measured the different components of the energy resolution (intrinsic, statistical, detector and electronic noise) vs. cell size, over-voltage and energy and we separated the different sources of excess noise factor.